The Implications of ChatGPT Usage on Students’ Critical Thinking Skills and Academic Integrity - Yulianti, Melia; Widiastuty, Erna (Akuntansi dan Teknologi Informasi, 2026)
Purpose –This study aims to analyze the impact of ChatGPT usage on critical thinking skills and academic integrity among accounting students. Methods – The independent variable, ChatGPT usage, is measured actual usage indicators, including frequency, manner, and purpose of use. The dependent variables consist of critical thinking skills, measured by interpretation, analysis, evaluation, inference, explanation, and self-regulation, and academic integrity, measured by honesty, trust, fairness, respect, responsibility, and courage.This research employs a quantitative method. Primary data were collected through a questionnaire distributed to accounting students in the city of Padang using purposive sampling. The sampling criteria included: (1) active accounting students, (2) students who had completed at least the third semester, and (3) students who had been using ChatGPT for more than one year Findings - The results indicate that ChatGPT usage has a positive effect on improving both critical thinking skills and academic integrity among accounting students in Padang. The findings imply that ethical use of ChatGPT can enhance students’ critical thinking abilities and academic integrity. But, the use of ChatGPT without ethical considerations may lead to academic integrity issues, including cheating and plagiarism. Therefore, higher education institutions are encouraged to establish policies and ethical guidelines to responsible use of ChatGPT in academic activities. Implications - This study contributes to the growing literature on artificial intelligence in higher education by demonstrating that ChatGPT can enhance students’ critical thinking skills and academic integrity when used responsibly. Additionaly, the findings provide practical insights for educators, universities, and policymakers to develop ethical guidelines, AI literacy programs, and instructional strategies that promote the responsible integration of generative AI tools into teaching and learning processes. Originality - This research is among the first studies to empirically investigate the dual influence of ChatGPT usage on critical thinking skills and academic integrity within accounting education. As such, the study offers a more comprehensive perspective on the educational consequences of generative AI adoption.